Undercover blues [videorecording (DVD)] - Abrams, Ian; Turner, Kathleen, 1954-; Quaid, Dennis; Shaw, Fiona, 1958-; Tucci, Stanley; Miller, Larry, 1953-; Thorin, Donald E.; Newman, David, 1954- (Metro-Goldwyn-Mayer, 2015)
A pair of super-spies on maternity leave are pressured into doing a case, with baby in tow.